Solid electrolyte coated metal doped silicon carbon composite material and preparation method thereof

By covering the solid electrolyte in the shell of the silicon-carbon composite, the problem of insufficient performance of the existing silicon-carbon composite is solved, and efficient ionic conductivity and electrochemical performance is achieved.

CN119890272APending Publication Date: 2025-04-25SICHUAN KUNTIAN NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510156155.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The ionic conductivity, rate performance and first-time efficiency of existing silicon-carbon composite materials are insufficient, making it difficult to meet the needs of high-performance battery materials.

Method used

The metal-doped silicon-carbon composite is coated with solid electrolyte, and the electron conductivity and ionic conductivity of the material are enhanced by depositing amorphous carbon in porous silicon and adding a solid electrolyte composite to the shell.

Benefits of technology

The first-time efficiency, cycle performance and rate performance of silicon-carbon composite materials have been significantly improved, and the transmission rate of lithium ions and the stability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890272A_ABST
    Figure CN119890272A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of silicon-carbon composite materials, and provides a solid electrolyte coated metal doped silicon-carbon composite material and a preparation method thereof. The solid electrolyte-coated metal-doped silicon-carbon composite material sequentially comprises an inner core and a shell from inside to outside, the inner core comprises porous silicon and amorphous carbon deposited in pores of the porous silicon; the porous carbon is doped with one or more of Li, Mg and O elements; the housing includes a solid electrolyte complex. According to the technical scheme, the problems of insufficient ionic conductivity, rate capability and initial efficiency of the silicon-carbon composite material in the related technology are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicon-carbon composite materials, and in particular to a solid electrolyte-coated metal-doped silicon-carbon composite material and a preparation method thereof. Background Art

[0002] The silicon-carbon composite material includes a core and a shell, the core is composed of porous carbon and nano-silicon deposited in the porous carbon pores, and the shell is amorphous carbon. However, due to the poor electronic conductivity of the porous carbon itself and the low temperature of its surface coating, the impedance of the amorphous carbon is large and there are defects. The interaction between the two causes the deviation of the dynamic performance of the silicon-carbon composite material and the low first efficiency. Although there are prior arts that improve the fast charging performance and first efficiency of silicon-carbon composite materials by doping non-metallic elements in the core or coating ionic compounds in the outer layer, for example, the invention patent with publication number CN116314670A discloses a silane cracking method to prepare cerium-doped amorphous carbon-coated silicon-carbon composite materials and their applications, the cerium-doped amorphous carbon-coated silicon-carbon composite material is a core-shell structure, the core is nitrogen-fluorine-doped nano-silicon porous carbon material, and the shell is cerium-doped amorphous carbon. Although the electronic conductivity of the material is improved, the improvement is not large, and the ionic conductivity and transmission rate of the silicon-carbon composite material are not improved, and the rate performance and first efficiency are insufficient.

[0003] Therefore, it is necessary to obtain a silicon-carbon composite material with excellent ionic conductivity, rate performance and first efficiency. Summary of the invention

[0004] The present invention provides a solid electrolyte coated metal-doped silicon-carbon composite material and a preparation method thereof, which solves the problem that the ionic conductivity, rate performance and first efficiency of the silicon-carbon composite material in the related art are insufficient.

[0005] The technical solution of the present invention is as follows: The present invention provides a solid electrolyte coated metal-doped silicon-carbon composite material, which includes a core and an outer shell from the inside to the outside; The core includes porous silicon and amorphous carbon deposited in the pores of the porous silicon; The porous carbon is also doped with one or more of Li, Mg, and O elements; The housing includes a solid electrolyte composite.

[0006] As a further technical solution, the mass of the shell is 1wt%~10wt% of the mass of the solid electrolyte-coated metal-doped silicon-carbon composite material.

[0007] The method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material according to the present invention comprises the following steps: S1, mixing nano silicon alloy, silicon dioxide and pore-forming agent, reacting to obtain porous silicon; S2, mixing a metal salt, a dispersant, and a solvent to obtain a mixture, adding the porous silicon to the mixture for reaction, and sintering to obtain metal-doped porous silicon carbon; S3, placing the metal-doped porous silicon-carbon in a silane mixed gas for deposition treatment to obtain a silicon-carbon composite material; S4, dispersing the solid electrolyte and dispersant into a solvent, adding the silicon-carbon composite material to continue dispersing, drying, carbonizing, and crushing to obtain a solid electrolyte-coated metal-doped silicon-carbon composite material.

[0008] In the present invention, nano silicon alloy is mixed with a pore former and its silicon dioxide. Under vacuum and high temperature conditions, the pore former decomposes to leave nano pores, and Fe, Mn, Al, and Mg in the silicon alloy react with concentrated nitric acid to generate gas and salt compounds thereof to form porous silicon, and part of the nano silicon reacts with silicon dioxide to generate silicon monoxide, thereby obtaining a honeycomb porous nano silicon / silicon monoxide composite material, which has the characteristics of weak activity and reduced occurrence of side reactions between the mixture in step S2 and the porous nano silicon / silicon monoxide composite material.

[0009] As a further technical solution, in step S1, the mass ratio of the nano-silicon alloy, silicon dioxide, and pore-forming agent is 100:50~100:5~20; In step S2, the mass ratio of the metal salt, the dispersant, and the porous silicon is 5-15:0.5-2:100, and the mass fraction of the metal salt in the mixture is 1wt%-10wt%; In step S4, the mass ratio of the solid electrolyte, the dispersant, the solvent, and the silicon-carbon composite material is 5-15:1-5:500-1500:100.

[0010] As a further technical solution, in step S1, the reaction is carried out in a vacuum environment of 1-10 Pa, the reaction temperature is 1200-1400° C., and the reaction time is 8-24 h; After the reaction, the first washing, filtering, second washing and drying treatments are performed in sequence; The first washing is acid washing; the second washing is water washing; The pickling is carried out by using hydrochloric acid and hydrofluoric acid in sequence; The mass concentration of the hydrochloric acid is 37%; The mass concentration of the hydrofluoric acid is 30% to 35%; In step S2, the reaction temperature is 50-100°C and the reaction time is 1-6 hours; The sintering temperature is 500-800°C and the sintering time is 1-6h; In step S3, during the deposition process, the vacuum is evacuated to 0.01-0.1 MPa, the temperature is 400-500° C., the flow rate of the silane mixed gas is 10-100 mL / min, and the time of introduction is 30-300 min; In step S4, the carbonization temperature is 600-1000° C. and the time is 2-12 hours.

[0011] As a further technical solution, in step S1, the nano silicon alloy comprises a nano silicon alloy having a silicon content of 40wt% to 80wt%, preferably, the nano silicon alloy comprises a nano silicon alloy having a silicon content of 40wt% to 50wt%, preferably, the nano silicon alloy comprises one or more of Si-Fe alloy powder, Si-Al alloy powder, Si-Mg alloy powder, and Si-Mn alloy powder; The pore-forming agent includes one or more of zinc chloride, zinc bromide, and zinc nitrate; In step S2, the metal salt includes one or more of metal chloride, nitrate, and sulfide; The metal includes magnesium or lithium; The dispersant includes one or more of sodium metaphosphate, polyvinyl pyrrolidone, oleate, sodium polyacrylate, polyethylene glycol, polyglycerol, ammonium polyacrylate, and ammonium citrate; In step S3, the silane mixed gas includes one or more of monosilane, disilane, dichlorosilane, dichlorodiethylsilane, and trisilane.

[0012] As a further technical solution, in step S4, the solid electrolyte includes one or more of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate, and aluminum lithium germanium phosphate; The dispersant includes one or more of sodium butylnaphthalene sulfonate, sodium arylnaphthalene sulfonate, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfate; In step S2 and step S4, the solvent includes one or more of cyclohexane, N-methylpyrrolidone, tetrahydrofuran, petroleum ether, and acetone.

[0013] As a further technical solution, the silicon dioxide is 3-amino-2-naphthol modified silicon dioxide.

[0014] In the present invention, 3-amino-2-naphthol is used to modify silicon dioxide to prepare a solid electrolyte-coated metal-doped silicon-carbon composite material, which further improves the initial efficiency of the silicon-carbon composite material and also improves the cycle performance.

[0015] As a further technical solution, in the raw materials of the 3-amino-2-naphthol-modified silica, the mass ratio of 3-amino-2-naphthol to silica is 1:12~15.

[0016] As a further technical solution, the preparation method of 3-amino-2-naphthol modified silica comprises the following steps: melting 3-amino-2-naphthol, mixing with silica, and cooling to obtain 3-amino-2-naphthol modified silica.

[0017] The working principle and beneficial effects of the present invention are: In the present invention, porous silicon is used and amorphous carbon is deposited in its pores to improve the electronic conductivity of the porous carbon and reduce side reactions, improve the electronic conductivity of the material and its carbon nanotubes constrain the expansion of nano-silicon, and improve the cycle performance.

[0018] In the present invention, a solid electrolyte is coated on the surface of a silicon-carbon composite material to obtain a solid electrolyte and a silicon-carbon composite material coated with a small amount of amorphous carbon, thereby reducing the side reaction of the inner core silicon-carbon and improving the initial efficiency. In addition, the high ionic conductivity of the solid electrolyte is utilized to reduce its irreversible capacity, improve the initial efficiency and the transmission rate of its lithium ions, and improve the rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0020] Figure 1 This is a SEM image of the solid electrolyte-coated metal-doped silicon-carbon composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] In the following examples and comparative examples, the Si content in the Si-Fe alloy powder is 40 wt %; the Si content in the Si-Al alloy powder is 45 wt %; and the Si content in the Si-Mg alloy powder is 50 wt %.

[0023] Example 1 A method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material comprises the following steps: S1. 100 g Si-Fe alloy powder, 80 g silicon dioxide and 10 g zinc chloride were mixed evenly and transferred to a vacuum furnace, evacuated to 5 Pa, reacted at 1300 ° C for 12 h, and then the obtained product was pickled with hydrochloric acid (1000 g) with a mass concentration of 37%, then soaked with hydrofluoric acid with a mass concentration of 30%, filtered, deionized and washed, and vacuum dried at 80 ° C for 24 h to obtain porous silicon; S2, adding 10g magnesium chloride and 1g sodium metaphosphate to 200g N-methylpyrrolidone to prepare a solution with a mass concentration of 5wt%, then adding 100g porous silicon to disperse evenly, reacting at a temperature of 80°C for 3h, filtering, and sintering the obtained filter residue at 650°C for 3h to obtain metal-doped porous silicon carbon; S3, transferring the metal-doped porous silicon carbon to a rotary kiln, evacuating to 0.05 MPa, heating to 450°C, and introducing a disilane mixed gas (the volume ratio of disilane to nitrogen is 1:2, and the flow rate is 50 mL / min) for 150 min to obtain a silicon-carbon composite material; S4. Add 10g of lithium lanthanum zirconium oxide and 3g of sodium butylnaphthalene sulfonate to 1000g of cyclohexane and disperse them evenly. Then add 100g of silicon-carbon composite material and disperse them evenly. Spray dry, carbonize and sinter at 800°C for 6h, crush and grade to obtain a solid electrolyte-coated metal-doped silicon-carbon composite material.

[0024] Example 2 A method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material comprises the following steps: S1. 100 g Si-Al alloy powder, 50 g silicon dioxide and 5 g zinc bromide were mixed evenly and transferred to a vacuum furnace. The mixture was evacuated to 1 Pa and reacted at 1200° C. for 24 h. The obtained product was pickled with 37% hydrochloric acid (1000 g) and then soaked with 35% hydrofluoric acid. The mixture was filtered, washed with deionized water and dried at 80° C. in vacuum for 24 h to obtain porous silicon. S2, adding 5g lithium chloride and 0.5g polyvinyl pyrrolidone to 500g N-methyl pyrrolidone to prepare a solution with a mass concentration of 1wt%, then adding 100g porous silicon to disperse evenly, reacting at a temperature of 50°C for 6h, filtering, and sintering the obtained filter residue at 500°C for 6h to obtain metal-doped porous silicon carbon; S3, transferring the metal-doped porous silicon carbon to a rotary kiln, evacuating to 0.01 MPa, heating to 400°C, and introducing a monosilane mixed gas (the volume ratio of monosilane to nitrogen is 1:1, and the flow rate is 10 mL / min) for 30 min to obtain a silicon-carbon composite material; S4. Add 5 g of lithium aluminum titanium phosphate and 3 g of sodium arylnaphthalene sulfonate to 500 g of N-methylpyrrolidone and disperse them evenly. Then add 100 g of silicon-carbon composite material and disperse them evenly. Spray dry, carbonize and sinter at 600 °C for 12 h, crush and grade to obtain a solid electrolyte-coated metal-doped silicon-carbon composite material.

[0025] Example 3 A method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material comprises the following steps: S1. 100 g Si-Mg alloy powder, 100 g silicon dioxide and 20 g zinc nitrate were mixed evenly and transferred to a vacuum furnace. The mixture was evacuated to 10 Pa and reacted at 1400 ° C for 8 h. The obtained product was pickled with hydrochloric acid (1000 g) with a mass concentration of 37%, and then soaked with hydrofluoric acid with a mass concentration of 30%, filtered, washed with deionized water, and dried at 80 ° C for 24 h to obtain porous silicon. S2, adding 15g of magnesium chloride and 2g of oleate to 150g of petroleum ether to prepare a solution with a mass concentration of 10wt%, then adding 100g of porous silicon to disperse evenly, reacting at a temperature of 100°C for 1h, filtering, and sintering the obtained filter residue at 800°C for 1h to obtain metal-doped porous silicon carbon; S3, transferring the metal-doped porous silicon carbon to a rotary kiln, evacuating to 0.1 MPa, heating to 500°C, and introducing a disilane mixed gas (the volume ratio of dichlorosilane and nitrogen is 1:3, and the flow rate is 100 mL / min) for 30 min to obtain a silicon-carbon composite material; S4. Add 15g of aluminum lithium germanium phosphide and 5g of sodium dodecylbenzene sulfonate to 1500g of acetone and disperse them evenly, then add 100g of silicon-carbon composite material and disperse them evenly, spray dry, carbonize and sinter at 1000°C for 2h, crush and grade to obtain a solid electrolyte-coated metal-doped silicon-carbon composite material.

[0026] Example 4 The difference between this example and Example 1 is that the silicon dioxide is replaced by 3-amino-2-naphthol modified silicon dioxide; The preparation method of 3-amino-2-naphthol modified silicon dioxide comprises the following steps: melting 3-amino-2-naphthol, mixing the mixture with silicon dioxide at a mass ratio of 1:12, and cooling the mixture to obtain 3-amino-2-naphthol modified silicon dioxide.

[0027] Example 5 The difference between this example and Example 1 is that the silicon dioxide is replaced by 3-amino-2-naphthol modified silicon dioxide; The preparation method of 3-amino-2-naphthol modified silicon dioxide comprises the following steps: melting 3-amino-2-naphthol, mixing the mixture with silicon dioxide at a mass ratio of 1:15, and cooling the mixture to obtain 3-amino-2-naphthol modified silicon dioxide.

[0028] Comparative Example 1 The difference between this comparative example and Example 1 is that zinc chloride is not added in step S1.

[0029] Comparative Example 2 The only difference between this comparative example and Example 1 is that the shell is not a solid electrolyte composite but amorphous carbon, that is, step S4 is: transfer 100g of the silicon-carbon composite material to a tubular furnace, heat it to 700°C, and introduce acetylene gas at a flow rate of 10mL / min for 60min to obtain an amorphous carbon-coated silicon-carbon composite material.

[0030] Comparative Example 3 The only difference between this comparative example and Example 3 is that the Si-Mg alloy powder is replaced by magnesium powder.

[0031] SEM Testing The solid electrolyte-coated metal-doped silicon-carbon composite material prepared in Example 1 was subjected to SEM testing, and the test results are as follows: Figure 1 As shown; Depend on Figure 1 It can be seen that the composite material prepared in Example 1 presents a granular structure with some microporous structures on the surface, and the particle size is between 5 and 10 μm.

[0032] Physical and chemical properties test The solid electrolyte-coated metal-doped silicon-carbon composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for tap density and specific surface area in accordance with GB / T 38823-2020 "Silicon Carbon"; the powder resistivity was tested by a four-probe tester; the pressure specific surface area was tested (test pressure 5T) by adding the solid electrolyte-coated metal-doped silicon-carbon composite materials to a tablet press; the true density was tested using a fully automatic true density tester; the test results are shown in Table 1.

[0033] Table 1 Physical and chemical properties test results

[0034] Button Cell Battery Test The solid electrolyte-coated metal-doped silicon-carbon composite materials in Examples 1 to 5 and Comparative Examples 1 to 3 are used as raw materials for the negative electrode material of lithium-ion batteries to assemble button batteries: The specific preparation method of the negative electrode sheet is as follows: adding a binder, a conductive agent and a solvent to a solid electrolyte-coated metal-doped silicon-carbon composite material, stirring to make a slurry, coating it on a copper foil, and drying and rolling to obtain the negative electrode sheet; The binder used is LA136D binder, the conductive agent is SP, the solvent is double distilled water, and the mass volume ratio of the solid electrolyte coated metal-doped silicon-carbon composite material, SP, LA136D, and double distilled water is 80g:15g:15g:300mL; The metal lithium sheet is used as the positive electrode; The electrolyte used was LiPF6 / EC+DEC, with LiPF6 at a concentration of 1.1 mol / L as the electrolyte and a mixture of EC and DEC at a volume ratio of 1:1 as the solvent; the diaphragm used a polypropylene PP film. The button cell was assembled in an argon-filled glove box, and the electrochemical performance was tested on a Wuhan Blue Electric CT2001A battery tester. The charge and discharge voltage range was 0.005V to 2.0V, and the charge and discharge rate was 0.1C. The first discharge capacity, first efficiency, charging DCR (50% SOC), and cycle performance (0.2C / 0.2C, 100 times) of the button cell were tested, and the button cell was tested at a fully charged 100% SOC, and the expansion rate of the negative electrode was dissected and tested; the test results are shown in Table 2.

[0035] Table 2 Button battery performance test results

[0036] It can be seen from Table 1 and Table 2 that the embodiment is better than the comparative example in the first discharge capacity, DCR, expansion and cycle performance. The reason is that the solid electrolyte coated on the surface of the material has high ion conductivity, high strength, reduced DCR and reduced expansion; at the same time, the irreversible capacity is low during the reaction between the solid electrolyte and lithium, which improves the first efficiency and improves the cycle performance.

[0037] Compared with Example 1, the solid electrolyte-coated metal-doped silicon-carbon composite materials prepared in Examples 4 to 5 are assembled into button-type batteries as raw materials for lithium-ion battery negative electrode materials, and the first discharge capacity, first efficiency, DCR, and cycle performance are all better, indicating that the solid electrolyte-coated metal-doped silicon-carbon composite materials are prepared by modifying silica with 3-amino-2-naphthol, which improves the electrochemical properties of the silicon-carbon composite materials, such as the first discharge capacity and first efficiency.

[0038] Soft pack battery test The solid electrolyte-coated metal-doped silicon-carbon composite material in Examples 1-3 and Comparative Examples 1-2 was mixed with 95% artificial graphite as the negative electrode, and the negative electrode sheet was prepared by slurry mixing and coating. 1 / 3 Co 1 / 3 Mn 1 / 3A 2Ah soft-pack battery was prepared using LiPO4 (O2) as the positive electrode, 1.3 mol / L LiPF6 (the solvent was EC and DEC in a volume ratio of 1:1) as the electrolyte, and Celgard2400 membrane as the separator.

[0039] The rate performance of the soft-pack battery was tested: the charge and discharge voltage range was 2.5~4.2V, the temperature was 25±3.0℃, and the resistance under different SOC conditions (90%, 70%, 50%, 30%, 10%, 5%) was tested at 3C, and the battery was discharged at 4.0C. The results are shown in Table 3.

[0040] Table 3 Soft pack battery rate performance test results

[0041] It can be seen from Table 3 that the impedance of the soft-pack battery of the solid electrolyte coated metal-doped silicon-carbon composite material prepared by the materials of Examples 1 to 3 is significantly lower than that of Comparative Examples 1 to 2, that is, the charging time is shorter. The reason for this is that lithium ions need to migrate during the battery charging process, the example materials have low powder resistivity and their solid electrolytes have strong liquid absorption capacity and high lithium ion conductivity, which reduces impedance and DCR.

[0042] The solid electrolyte-coated metal-doped silicon-carbon composite material in Examples 1 to 5 and Comparative Examples 1 to 3 was mixed with 95% artificial graphite as the negative electrode, and the negative electrode sheet was prepared by slurry mixing and coating. 1 / 3 Co 1 / 3 Mn 1 / 3 A 2Ah soft-pack battery was prepared using LiPO4 (O2) as the positive electrode, 1.3 mol / L LiPF6 (the solvent was EC and DEC in a volume ratio of 1:1) as the electrolyte, and Celgard2400 membrane as the separator.

[0043] Cycle performance: The obtained soft-pack battery was subjected to a cycle performance test. The test conditions were: charge and discharge current 1C / 1C, voltage range 2.5~4.2V, cycle number 500 times. The test results are shown in Table 4.

[0044] Table 4 Soft pack battery cycle performance test results

[0045] It can be seen from Table 4 that the cycle performance of the lithium-ion battery prepared by using the solid electrolyte coated metal-doped silicon-carbon composite material obtained in Examples 1 to 3 is significantly better than that of the comparative example. The experimental results show that the reason is that the example material has low expansion and low powder resistivity, which reduces the lithium ions consumed by repeated repair of SEI during charging and discharging, and improves the cycle performance.

[0046] Compared with Example 1, the solid electrolyte-coated metal-doped silicon-carbon composite material prepared in Examples 4 to 5 is used as the raw material for the negative electrode material of a lithium-ion battery. After being assembled into a soft-pack battery, the retention rate after 500 cycles is higher, indicating that the solid electrolyte-coated metal-doped silicon-carbon composite material is prepared by modifying silica with 3-amino-2-naphthol, thereby improving the cycle performance of the silicon-carbon composite material.

[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A solid electrolyte coated metal-doped silicon-carbon composite material, characterized in that: From the inside out, it includes the core and the shell; The core includes porous silicon and amorphous carbon deposited in the pores of the porous silicon; The porous carbon is also doped with one or more of Li, Mg, and O elements; The housing includes a solid electrolyte composite.

2. The solid electrolyte-coated metal-doped silicon-carbon composite material according to claim 1, characterized in that: The mass of the shell is 1wt% to 10wt% of the mass of the solid electrolyte-coated metal-doped silicon-carbon composite material.

3. The method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, mixing nano silicon alloy, silicon dioxide and pore-forming agent, reacting to obtain porous silicon; S2, mixing a metal salt, a dispersant, and a solvent to obtain a mixture, adding the porous silicon to the mixture for reaction, and sintering to obtain metal-doped porous silicon carbon; S3, placing the metal-doped porous silicon-carbon in a silane mixed gas for deposition treatment to obtain a silicon-carbon composite material; S4, dispersing the solid electrolyte and dispersant into a solvent, adding the silicon-carbon composite material to continue dispersing, drying, carbonizing, and crushing to obtain a solid electrolyte-coated metal-doped silicon-carbon composite material.

4. The method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material according to claim 3, characterized in that: In step S1, the mass ratio of the nano-silicon alloy, silicon dioxide, and pore-forming agent is 100:50-100:5-20; In step S2, the mass ratio of the metal salt, the dispersant, and the porous silicon is 5-15:0.5-2:100, and the mass fraction of the metal salt in the mixture is 1wt%-10wt%; In step S4, the mass ratio of the solid electrolyte, the dispersant, the solvent, and the silicon-carbon composite material is 5-15:1-5:500-1500:

100.

5. The method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material according to claim 4, characterized in that: In step S1, the reaction is carried out in a vacuum environment of 1-10 Pa, the reaction temperature is 1200-1400° C., and the reaction time is 8-24 h; After the reaction, the first washing, filtering, second washing and drying treatments are performed in sequence; The first washing is acid washing; the second washing is water washing; In step S2, the reaction temperature is 50-100°C and the reaction time is 1-6 hours; The sintering temperature is 500-800°C and the sintering time is 1-6h; In step S3, during the deposition process, the vacuum is evacuated to 0.01-0.1 MPa, the temperature is 400-500° C., the flow rate of the silane mixed gas is 10-100 mL / min, and the time of introduction is 30-300 min; In step S4, the carbonization temperature is 600-1000° C. and the time is 2-12 hours.

6. The method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material according to claim 4, characterized in that: In step S1, the nano-silicon alloy comprises a nano-silicon alloy having a silicon content of 40wt% to 80wt%, and preferably, the nano-silicon alloy comprises one or more of Si-Fe alloy powder, Si-Al alloy powder, Si-Mg alloy powder, and Si-Mn alloy powder; The pore-forming agent includes one or more of zinc chloride, zinc bromide, and zinc nitrate; In step S2, the metal salt includes one or more of a chloride, a nitrate, and a sulfide of a metal, and the metal includes magnesium or lithium; The dispersant includes one or more of sodium metaphosphate, polyvinyl pyrrolidone, oleate, sodium polyacrylate, polyethylene glycol, polyglycerol, ammonium polyacrylate, and ammonium citrate; In step S3, the silane mixed gas includes one or more of monosilane, disilane, dichlorosilane, dichlorodiethylsilane, and trisilane.

7. The method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material according to claim 4, characterized in that: In step S4, the solid electrolyte includes one or more of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate, and aluminum lithium germanium phosphate; The dispersant includes one or more of sodium butylnaphthalene sulfonate, sodium arylnaphthalene sulfonate, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfate; In step S2 and step S4, the solvent includes one or more of cyclohexane, N-methylpyrrolidone, tetrahydrofuran, petroleum ether, and acetone.

8. The method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material according to claim 4, characterized in that: The silicon dioxide is 3-amino-2-naphthol modified silicon dioxide.

9. The method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material according to claim 8, characterized in that: In the raw materials of the 3-amino-2-naphthol-modified silica, the mass ratio of 3-amino-2-naphthol to silica is 1:12-15.

10. The method for preparing a solid electrolyte-coated metal-doped silicon-carbon composite material according to claim 9, characterized in that: The preparation method of 3-amino-2-naphthol modified silicon dioxide comprises the following steps: melting 3-amino-2-naphthol, mixing the mixture with silicon dioxide, and cooling the mixture to obtain 3-amino-2-naphthol modified silicon dioxide.

Citation Information

Patent Citations

  • Cerium-doped amorphous carbon coated silicon-carbon composite material prepared by silane cracking method and application of cerium-doped amorphous carbon coated silicon-carbon composite material

    CN116314670A